Genitourinary malformations: an under-recognized feature of ectrodactyly, ectodermal dysplasia and cleft lip/palate syndrome. Issue 2 (April 2017) - Hyder, Zerin; Beale, Victoria; O'Connor, Ruth; Clayton-Smith, Jill
Abstract : The ectodermal dysplasia and cleft lip/palate (EEC) syndrome describes the association of ectrodactyly, ectodermal dysplasia and orofacial clefting. As with many autosomal dominant disorders, there is variability in expression and not all of these three core features are present in every individual with the condition. Moreover, there may be additional associated features, which are under-recognized. One of these is the presence of genitourinary anomalies, some of which cause significant morbidity. This report details a further two patients with EEC syndrome and genitourinary involvement, including flaccid megacystis with detrusor muscle failure, bilateral hydronephrosis and megaureter, requiring significant renal and urological involvement during their childhood. We go on to review the literature on the diagnosis and management of genitourinary malformations in EEC syndrome.